An Indonesian Islamic University: How is it Possible - Fuad Jabali (Studia Islamika, 2004)
This document explains about the transformation from IAIN (Institut Agama Islam Negeri, State Institute for Islamic Studies) into UIN which has many significant consequences. First, academically; while in IAIN only Islamic Studies (such as theology, Islamic jurisprudence and exegesis) are developed, in UIN the scope of studies broadens to include 'secular' sciences. Second, while most of students of IAIN are mainly from madrasah/pesantren/rural communities. UIN, with its secular faculties, attracts a wider variety of students from a more heterogeneous background.DOI: 10.15408/sdi.v11i3.600